(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2009)
One of problems we find in the field of the epistemology of social sciences and which is related directly with the knowledge of the other, has to do with the processes that a subject suffers when he tries to go from the constitution of meanings to the interpretative constitutions, especially in the conscience of the actor/observer. This phenomenon has a particular relevance if we pretend to establish some distinctions in the context of intersubjetive relationships. In the present work we have as a purpose to design and comment about some distinctions we observe in the processes of the constitution of meaning, from a perspective that transcends purely empirical antecedents. To tackle this study we will make use of some of the approaches of Weber, Husserl, Parsons and Schütz, since they, from a direct or indirect way, had given origin to a line of research different from the positivistic tradition.